Spatiotemporal distribution of power outages with climate events and social vulnerability in the USA - Do, Vivian; McBrien, Heather; Flores, Nina M.; Northrop, Alexander J.; Schlegelmilch, Jeffrey; Kiang, Mathew V.; Casey, Joan A. (Nature communications, 2023)
Power outages threaten public health. While outages will likely increase with climate change, an aging electrical grid, and increased energy demand, little is known about their frequency and distribution within states. Here, we characterize 2018–2020 outages, finding an average of 520 million customer-hours total without power annually across 2447 US counties (73.7% of the US population). 17,484 8+ hour outages (a medically-relevant duration with potential health consequences) and 231,174 1+ hour outages took place, with greatest prevalence in Northeastern, Southern, and Appalachian counties. Arkansas, Louisiana, and Michigan counties experience a dual burden of frequent 8+ hour outages and high social vulnerability and prevalence of electricity-dependent durable medical equipment use. 62.1% of 8+ hour outages co-occur with extreme weather/climate events, particularly heavy precipitation, anomalous heat, and tropical cyclones. Results could support future large-scale epidemiology studies, inform equitable disaster preparedness and response, and prioritize geographic areas for resource allocation and interventions. The authors find within-day, seasonal, and regional differences in county-level power outages from 2018–2020. Outages commonly co-occur with climate events. Counties in the south and Michigan faced high social and medical vulnerabilities and outages.